Philosophy and Public Administration: Philosophy and Public Administration - Edoardo Ongaro (Edward Elgar Publishing, 2020)
Philosophy and Public Administration provides a systematic and comprehensive introduction to the philosophical foundations of the study and practice of public administration. In this revised second edition, Edoardo Ongaro offers an accessible guide for improving public administration, exploring connections between basic ontological and epistemological stances and public governance, while offering insights for researching and teaching philosophy for public administration in university programmes.